Diagnostic Yield of Bronchoalveolar Lavage in Nepalese Patients Presenting with Chronic Cough with Normal Radiological Imaging in Tertiary Care Hospital - Shahi, Rejina; Bhatta, Narendra; Raj Mishra, Deebya; Verma, Avatar; Upreti, Augraj; Aryal, Prakash; Yadav, Devesh Kumar; Regmi, Gunjan (Nepalese Respiratory Journal, 2022)
Background: Cough is one of the most common symptoms that lead patients to seek medical attention. The diagnosis of chronic cough is complex and challenging. In our setting, a large proportion of patients with cough are treated empirically without a definite diagnosis. Despite investigation and treatment, fiberoptic bronchoscope with bronchoalveolar lavage (BAL) has been shown to be a useful technique in a selected group of patients with unexplained chronic persistent cough. The aim of the study was to determine the diagnostic yield of bronchoalveolar lavage in Nepalese patients presenting with chronic cough with normal radiological imaging. Methods: This was a hospital based cross sectional study. The patients presenting with chronic cough (>8 weeks) with normal radiological imaging were enrolled in the study. Results: 1 patient (2.6%) sputum sample for AFB was negative however BAL sample of the same patient sent for Gene xpert came positive for Mycobacterium Tuberculosis, 5 patients (12.8%) had positive BAL culture, 29 patients (74.4%) had normal cellular pattern in BAL Cytology. Conclusion: Diagnostic yield of BAL was very low for chronic cough in our study. Patient presenting with eosinophilic pattern in BAL had cough variant asthma suffer from non-productive cough in the absence of other asthma symptoms such as dyspnea and wheezing. Thus, though fiberoptic bronchoscope with BAL is indicated in chronic cough of unknown etiology, its diagnostic yield is low